Regional Variations in Social Development and Levels Of Living- A Study of the Impact of Plan Programme Volume II - Programme Evaluation Organisation, Planning Commission (Programme Evaluation Organisation, Planning Commission, Government of India, 1968)
The study on Regional Variations in Social Development and Levels of Living, conducted by the Programme Evaluation Organisation under the Planning Commission of India, presents a comprehensive assessment of inter-state and inter-regional disparities in socio-economic development since the inception of planned economic growth in 1955. Covering critical sectors such as agricultural practices, minor irrigation, soil conservation, educational access, drinking water supply, rural health services, transport connectivity, and village infrastructure, the report reveals significant inequalities across states and regions. Progressive states like Punjab and Gujarat demonstrate high adoption of improved agricultural inputs and better irrigation coverage, while eastern and central regions lag behind in productivity and infrastructure. Soil conservation efforts and irrigation maintenance vary widely, directly influencing agricultural yields. Educational access shows marked imbalances, particularly at the secondary level and in teacher training standards, while disparities in safe drinking water, protected wells, and public health facilities highlight persistent rural vulnerabilities. Transport infrastructure—including bus stops, railway stations, and market centers—remains unevenly distributed, affecting economic integration and service delivery. Agricultural statistics further illustrate wide differences in crop area distribution and productivity among states. The findings underscore the urgent need for targeted, region-specific policy interventions aimed at strengthening agricultural modernization, expanding educational and health infrastructure, improving water security, and enhancing rural connectivity to achieve balanced regional growth and equitable improvements in living standards across India.
Programme Evaluation Organisation Planning Commission Government of India 1968
Keywords: Programme Evaluation Organisation; Planning Commission of India; Regional Development Disparities; Agricultural Practices Adoption; Minor Irrigation Facilities; Soil Conservation Measures; Rural Drinking Water Supply; Educational Infrastructure Access; Rural Health Services; Village Transport Connectivity; Crop Area Distribution; Balanced Regional Growth